Mental Health Response Vehicles in Wales: A Pilot Initiative - Mark Jones (BJPsych Open)
Aims: Emergency NHS services are under considerable pressures from patient demand and ineffectual care and social pathways. This is especially felt within the mental health services where demand has grown from long periods of austerity and the Covid pandemic. To reduce demand on both ambulances and emergency departments Welsh ambulance implemented the roll out of mental health practitioners within its 999 call centres which has been very successful, however, the successful closure/treatment rate is less than half the callers. Over half of all mental health 999 callers require face to face intervention therefore ambulances within Wales need to implement mental health response vehicles in order to achieve this.